The Graduate Tracking and Attainment Model at the University of Pécs - SIPOS, NORBERT; KURÁTH, GABRIELLA (Journal of Education Culture and Society, 2020)
The aim of this study is to provide an overview of the Hungarian higher education system facing changes since 1990. The three major challenges are: the decreasing number of students enrolling since the ‘golden age’ ended; the Bologna-Process and its influence since its introduction in 2006 and the uncertainty about the future role of the state in educational finance. The institutions have to take these changes and the effects on their situation into account and they need to flnd a way to benefit from them. Thanks to Graduate Follow-Up System (GFS) research, they can measure the new graduates performance on the labour–market, their job-related satisfaction levels and possibilities, and furthermore they can have direct information about employers’ expectations, first of all on the level of working skills. This information can be used for the creation of a different approach of how to think about the students and which services could be offered to them. In the following analysis we use data from research conducted in the last three years at the University of Pécs.The focused energy and resource investment is more effective if it is based on specific training and education packages offered within the Alumni framework. It can increase the results of an even more successful Alma Mater service; furthermore it can improve the self-identification of the institution, therefore it is important to have a long-term strategy.